ANALISIS PROSES PENGADAAN MATERIAL PROYEK KONVENSIONAL DAN PROYEK ENGINEERING PROCUREMENT CONSTRUCTION (EPC) (Studi Kasus : Proyek Pembangunan Gunawangsa MERR Apartement Surabaya dan Proyek EPC 1 Banyu Urip Cepu) - Moh. Nur Sholeh; Shifa Fauziyah; M. Agung Wibowo; Frida Kistiani (Jurnal Karya Teknik Sipil, 2014)
Nowadays, construction project has been progressing well, it uses new technologies, materials and contract models. A new contract model is EPC (Engineering, Procurement and Construction). At Conventional contract, commonly used in highrise building projects which involves many participants such as owner, design consultant, general contractor, and management construction consultant. While, Engineering, Procurement and Construction (EPC) project involves general contractor only. In EPC project general contractor is the main actor in the engineering process, procurement until construction. EPC Contract is suitable to build facility of processing oil and gas. This research uses the project of Gunawangsa MERR Apartment and EPC 1 Banyu Urip as case studies of conventional project and EPC’s project. The goals are to analyze procurement organization and procurement material process at conventional project and EPC project, also to find out the weakness and strength of material procurement process from the both projects. The procurement process of materials on EPC projects uses the Material Tracking System (MTS) to manage the procurement process of materials because of the complexity of the project. In addition, the project EPC uses materials and equipments that have special specifications and are not available in the market so we need a system to manage the process of ordering, fabrication until materials can be delivered on time so it will not make any delays in the project. Because the material procurement process in EPC projects require time for fabrication so that procurement of materials has been performed on engineering phase. Therefore, the EPC project has its own material procurement organization which is directly supervised by a procurement manager. Where any personnel involved have a clear task.Meanwhile , the conventional material procurement project carried out by the logistics which is directly supervised by a project manager for the material procurement process which is much more simple when compared with Material Tracking System in EPC. In addition, the materials of conventional project are available in the market so that procurement is not through a specific manufacturing process and is often performed on construction phase. However, because the procurement process is undertaken during construction so that when there is a problem or difficulty in getting material it  will result any  project delays.